2017
DOI: 10.5267/j.msl.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Customer equity of Pakistani fast food restaurant: A study of attitudinal customer equity

Abstract: Customer Equity is true representative of relationship marketing. There are two major approaches to measure Customer Equity: Transaction/sales based approach and Attitudinal Approach. This research is an effort to check customer equity of fast food restaurants of Pakistan by using attitudinal approach. Transactional customer equity is treated as criterion for attitudinal customer equity. Three drivers of Customer Equity are Value Equity, Brand equity and Relationship equity are taken as independent variables i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We also provide an intervening process through which FFA turns into FFAC. Several consumer behavioural studies explain what causes FFA (Goyal & Singh, 2007; Nawaz et al, 2017), for example, quantitative findings of previous studies suggest that cravings for and impulsiveness towards fast‐food have a significant relation with FFA (Khalid et al, 2019). A recent study found FFA is the result of personal, social, and advertising factors (Aydin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also provide an intervening process through which FFA turns into FFAC. Several consumer behavioural studies explain what causes FFA (Goyal & Singh, 2007; Nawaz et al, 2017), for example, quantitative findings of previous studies suggest that cravings for and impulsiveness towards fast‐food have a significant relation with FFA (Khalid et al, 2019). A recent study found FFA is the result of personal, social, and advertising factors (Aydin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Majabadi et al (2016) found that many study participants reported health concerns as a major factor discouraging fast‐food consumption. So, FFAC motives discourage consumption for health and sustainability reasons (Lim, 2017; Nawaz et al, 2017). Furthermore, researchers suggest that anti‐consumption is relevant to FFA due to (1) impulse buying (Upadhye et al, 2021), (2) compulsive buying (Pradhan et al, 2018), and (3) food addiction, which is an uncontrolled and obsessive syndrome where consumer's experience strong pleasure‐seeking impulses and cravings (Adriaanse et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the informal sector existing is street vendors. On the basis of spiritual motivation, work culture and work ethos, and encouraged by the level of service quality and customer satisfaction (Nawaz et al, 2017), the research is conducted in relation to spiritual motivation, work culture and work ethos as predictors of merchant satisfaction through service quality of street vendors in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Organizations should consider CSR practices not only as a moral obligation but also as a strategic business decision that can positively impact their brand equity and financial performance (Nawaz et al, 2017). By demonstrating their commitment to social and environmental responsibility, organizations can build trust and loyalty with their customers, employees, and other stakeholders (Hayat et al, 2022).…”
Section: Factors That Influence Customers' Perceptions Of the Companymentioning
confidence: 99%